2013
DOI: 10.4212/cjhp.v66i4.1267
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Clinical Pharmacy Interventions in the Intensive Care Unit

Abstract: Documenting clinical pharmacy activities is essential for assessing pharmacists' impact on patient outcomes. These data suggest that ICU pharmacists prioritize clinical activities to care for the sickest patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Documentation of pharmacy activities is an important component of clinical pharmacy services. The documentation of clinical pharmacy activities and the ability to identify pharmacists’ interventions are essential for assessing their impact on patient outcomes [ 22 ]. The fact that only 44 % of the surveyed hospitals documented the clinical pharmacy service they had provided strongly indicates that a system needs to be designed where services rendered could be documented and evaluated when the need arises.…”
Section: Discussionmentioning
confidence: 99%
“…Documentation of pharmacy activities is an important component of clinical pharmacy services. The documentation of clinical pharmacy activities and the ability to identify pharmacists’ interventions are essential for assessing their impact on patient outcomes [ 22 ]. The fact that only 44 % of the surveyed hospitals documented the clinical pharmacy service they had provided strongly indicates that a system needs to be designed where services rendered could be documented and evaluated when the need arises.…”
Section: Discussionmentioning
confidence: 99%
“…The role of clinical pharmacists in reducing medication errors has been widely discussed in the literature. Interventions by clinical pharmacists have been shown to improve patient safety, satisfaction and compliance rates as well as decreasing adverse drug events and the length of hospital stay (Leape et al, 1999 ; Moffett et al, 2008 ; Makowsky et al, 2009 ; Klopotowska et al, 2010 ; Cunningham, 2012 ; Kelishadi and Mousavinasab, 2012 ; Zhang et al, 2012 ; Ho et al, 2013 ; Jiang et al, 2014 ; Zhai et al, 2015 ). Some studies have shown considerable cost savings (Krupicka et al, 2002 ; Larochelle et al, 2012 ; Lucca et al, 2012 ; Michalets et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to severity of illness and major changes in organ function, critically ill patients have complex and changing pharmacokinetics and pharmacodynamics, requiring careful evaluation and drug therapy management. Considerable evidence supports the value of having clinical pharmacists (CPs) in ICUs during multidisciplinary critical care 2‐9 . In addition, numerous pharmaceutical economics studies have shown that pharmaceutical intervention can lead to cost savings 10‐18 …”
Section: What Is Known and Objectivementioning
confidence: 99%